Temperature and pH Optimization of Chitin from Shrimp Skin as Adsorbent for Textile Dye Waste - Manik, Melani Indah Sari; Satyantini, Woro Hastuti; Mubarak, Ahmad Shofy (Bioscientist : Jurnal Ilmiah Biologi, 2024)
Textile waste consists of insoluble solid particles, salts, dyes and heavy metals and is very difficult to degrade. Chitin derived from shrimp waste has the potential to overcome textile waste in chitin that causes environmental pollution through more economical absorption and easily available raw materials. Factors that improve adsorption performance include pH and temperature. This study was conducted to determine the effect of temperature, pH, and a combination of temperature and pH treatments on the ability of chitin to adsorb textile dye waste. The parameters observed were temperature, pH, combination of temperature and pH, functional groups (FTIR), chitin structure (SEM), and heavy metal test (AAS). Data analysis of statistical test results using two-way Analysis of Variance (ANOVA) followed by Duncan’s further test. The ANOVA test results showed that the incubation treatment of temperature, pH, and a combination of different temperature and pH treatments resulted in (p < 0.05). This shows that incubation temperature and pH have an effect (significantly different) on the adsorption of chitin as an adsorbent on dyes. The results of Duncan’s test showed that the best chitin adsorption was obtained in temperature incubation at 50Â°C (A3), incubation at pH 3 (B1), and the best combination adsorption at 50Â°C and pH 3 of 1,091Â±0.007a ppm.